Differential Responses of Taxonomic, Structural, and Functional Diversity to Local-Scale Environmental Variation in Afromontane Forests in South Africa - Mensah, Sylvanus; SALAKO, Kolawolé Valère; ASSOGBADJO, ACHILLE EPHREM; Glèlè Kakaï, Romain Lucas (My University, 2018)
Exploring taxonomic, functional, and structural diversity can provide additional insights into our understanding of diversity responses to environment. Using altitude, slope, and relative radiation index as well as floristic and functional data from a South Africa Afromontane forest, we examined how taxonomic, structural, and functional diversity varied with local environmental variation. Taxonomic and structural diversity were quantified through species richness- and diameter class-based Shannon index and evenness, respectively. Skewness and coefficient of variation of diameter distribution were additionally computed for structural diversity. As for functional diversity, we used functional richness, evenness, divergence, and dispersion based on functional traits. Data were analyzed using multimodel inference and subset regression. We found little evidence of environmental effects on local-scale taxonomic diversity patterns. In contrast, structural and functional diversity metrics varied significantly along environmental gradients. Accordingly, diameter class-based Shannon evenness declined with increasing slope while skewness and coefficient of variation of diameter distribution increased with increasing slope. Functional evenness and divergence decreased with increasing altitude and radiation, respectively, while functional richness and dispersion increased with increasing slope. The results showed that taxonomic diversity patterns were less responsive to local-scale topographical variation than structural and functional diversity. Lower functional diversity on lower slope sites suggests weak environmental filtering effect promoting competitive exclusion and dominance of species with acquisitive traits. On higher slope sites, environmental filtering associated with slope gradient seems to favor coexistence of species with conservative traits and adapted to harsh conditions.
Keywords: diversity patterns; environmental filtering; radiation index; species coexistence; slope